28.5: Research and Realization of Picture Quality Calibration Technology in Monitor System. (26th August 2021) - Wang, Xian; Rao, Tianmin; Lin, Yilin; Duan, Ran; Geng, Lihua; Ma, Xitong
Abstract : Picture quality calibration technology plays an important role in the display system. The focus of the radio and television system is to obtain the best visual experience, and many of them include beautifying images and pleasing the audience. And the focus of the professional monitor system is to restore the live effects of the camera and other film sources to the greatest extent. This paper introduces the image quality calibration technology in the monitor system, mainly around the color temperature, gamma and color gamut calibration technology, and realizes the automatic calibration process. This method has been successfully applied to the image quality calibration work of monitor products. It liberates human resources, significantly improves the efficiency of R&D and testing of monitor products, and greatly promotes the mass production of monitor products.